Stability and convergence analysis of singular integral equations for unequal arms branch crack problems in plane elasticity - Ghorbanpoor, R.; J., Saberi-Nadjafi; Nik Long, N. M .A.; M., Erfanian (Elsevier, 2022)
In this paper, an unequal arms branch crack problem in a plane elasticity is treated. Using distribution dislocation function and complex variable potential method, the problem is formulated into a singular integral equation. The appropriate integration scheme, in which a point dislocation is set at the origin and the distribution dislocation, is applied through all arms of the branch crack to solve the obtained singular integral equations numerically. Stability, convergence, the order of convergence, and the error term of the solution are analyzed. Some numerical examples are examined to describe the behavior of stress intensity factors at the endpoints of each branch crack.